Penerapan Model Cooperative Learning Tipe Stad pada Pembelajaran Matematika Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik di Kelas V SDN 122 /X Sungai Beras Semester Ganjil Tahun Pelajaran 2022/2023 - Kholid Kholid (Journal on Education, 2022)
This study aims to describe and obtain information on improving mathematics learning outcomes through the STAD Type Cooperative Learning Model. This research is a classroom action research which consists of two cycles, each cycle consists of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were 35 students in class V at SDN 122/X Sungai Beras. This research was conducted in the odd semester of the 2022/2023 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through the STAD Type Cooperative Learning Model it could improve the mathematics learning outcomes of fifth grade students at SDN 122/X Sungai Beras by giving rewards